Andragogy reflection - contemporary specifics of the discipline - Zofia Szarota; Krzysztof Pierścieniak (Studia z Teorii Wychowania)
Andragogy, as a young discipline, is faced with a number of theories of theory and methodology. The aim of the study was to identify the dominant threads in andragogists' publications and to determine what complexes of problems and thematic issues determine today's specificity of the sub-discipline. In the process of analyzing the content of articles from the area of social sciences published in the pages of andragogical journals, a non-reactive method of document analysis was used. Five analytical andragogical categories were identified and included in the typology developed for the purposes of the study.